STRUKTUR KEPEMILIKAN, RISIKO, DAN KEBIJAKAN KEUANGAN: ANALISIS PERSAMAAN SIMULTAN - Ismiyanti, Fitri; Hanafi, Mamduh M. (Journal of Indonesian Economy and Business, 2004)
The research explores using simultaneous regression, to examine the interdependencerelationship between managerial ownership, risk, dividend policy, institutional ownership,and leverage policy for Indonesian capital market. The research tries to explain how therelationships in financial policy for manufacture firms in Indonesia. We use five models ofregression to represent five different policies in firms that reflect the agency issues andconflict of interest between agent (manager), and principal (insider and outsidershareholders). Jensen and Meckling (1976) argued that agency problem arise fromseparation of ownership and control. Each of five policies in this research is representconflict of interest between agent and principal. The research combined models fromCrutchley, Jensen, Jahera and Raymond (1999), and Chen and Steiner (1999) to construct five-regression policies model.We find interdependence relationship between managerial ownership, risk, dividendpolicy, institutional ownership, and leverage policy. We also find substitution effectbetween dividend policy and managerial ownership, and between managerial ownershipand institutional ownership as predicted by agency theory. The substitution effect showedthat ownership structure effectively used to reduce the agency problem between agent and principal. The study confirms that the relationship between risk and dividend is non-linear.Keyword: Agency Theory; Managerial Ownership; Risk; Dividend Policy; Debt Policy.